Crustal reworking in a shear zone: transformation of metagranite to migmatite. (19th February 2016) - Carvalho, B. B.; Sawyer, E. W.; Janasi, V. A.
Abstract: This study uses field, microstructural and geochemical data to investigate the processes contributing to the petrological diversity that arises when granitic continental crust is reworked. The Kinawa migmatite formed when Archean TTG crust in the São Francisco Craton, Brazil was reworked by partial melting at ~730 °C and 5–6 kbar in a regional‐scale shear zone. As a result, a relatively uniform leucogranodiorite protolith produced compositionally and microstructurally diverse diatexites and leucosomes. All outcrops of migmatite display either a magmatic foliation, flow banding or transposed leucosomes and indicate strong, melt‐present shearing. There are three types of diatexite. Grey diatexites are interpreted to be residuum, although melt segregation was incomplete in some samples. Biotite stable, H2 O‐fluxed melting is inferred via the reaction Pl + Kfs + Qz + H2 O = melt and geochemical modelling indicates 0.35–0.40 partial melting. Schlieren diatexites are extremely heterogeneous; residuum‐rich domains alternate with leucocratic quartzofeldspathic domains. Homogeneous diatexites have the highest SiO2 and K2 O contents and are coarse‐grained, leucocratic rocks. Homogeneous diatexites, quartzofeldspathic domains from the schlieren diatexites and the leucosomes contain both plagioclase‐dominated and K‐feldspar‐dominated feldspar framework microstructures and hence were melt‐derived rocks. Both types of feldspar frameworks show evidence of tectonic compaction. Modelling the crystallization of an initial anatectic melt shows plagioclase appears first; K‐feldspar appears after ~40% crystallization. In the active shear zone setting, shear‐enhanced compaction provided an essentially continuous driving force for segregation. Thus, Kinawa migmatites with plagioclase frameworks are interpreted to have formed by shear‐enhanced compaction early in the crystallization of anatectic melt, whereas those with K‐feldspar frameworks formed later from the expelled fractionated melt. Trace element abundances in some biotite and plagioclase from the fractionated melt‐derived rocks indicate that these entrained minerals were derived from the wall rocks. Results from the Kinawa migmatites indicate that the key factor in generating petrological diversity during crustal reworking is that shear‐enhanced compaction drove melt segregation throughout the period that melt was present in the rocks. Segregation of melt during melting produced residuum and anatectic melt and their mixtures, whereas segregation during crystallization resulted in crystal fractionation and generated diverse plagioclase‐rich rocks and fractionated melts.